Pengabdian Masyarakat ke Mushola Baitur Rahim Kabupaten Deli Serdang Dengan Pemberian Alat Pencuci Tangan - Ahmad Yanie; J Junaidi; Fadly Ahmad Kurniawan Nst; Indra Roza; Din Aswan Amran Ritonga; E Eddy (LPPM STIKOM Tunas Bangsa, 2021)
Community service is one of the cores of the foundation's permanent lecturers' implementation of the Tri Dharma College policy at the Faculty of Engineering and Computers, Universitas Harapan Medan. Therefore, we from the Engineering lecturers at Harapan University Medan have a plan to provide a hand washing device which aims to participate in tackling the spread of covid-19. This hand washing tool uses an automatic system using an electric sensor. Where the system works, if we are going to wash our hands and right in the middle position, the water will come out of the discharge pipe, so it is not difficult for the water to come out of the pipe, there is no need to turn or press the faucet. So that the hand washing tool works automatically and economically, it is also not easily damaged.